Milo Urban’s Journalist Writing and Memoirs on the Theme of the Holocaust (in Slovak literature) - Csiba, Karol (Poznańskie Studia Slawistyczne, 2017)
The article discusses selected texts of different genres by Milo Urban (1904–1982). The first text level is represented by fragments from his memoirs written in the 1970s and only published in the 1990s. An analysis of Urban’s journalistic activities during the Second World War provides us with another point of view. The article wishes to show different language versions elaborated by one author when dealing with one particular historical moment (the solution of the Jewish question and the Holocaust). This points at a significant change in Urban’s attitude to historical tragedies of the 20th century, and raises the question about a personal tragedy of an individual as well as his ability to cope with guilt and responsibility.